Legal Position of Employees Post Spin off PT Perkebunan Nusantara III (Persero)Medan Operations Become PT Perkebunan Nusantara IV (Study at PT Perkebunan Nusantara IV Regional I) - Abdi, Muhammad Parrij; Siregar, Mahmul; Agusmidah (Universitas Sumatera Utara, 2025)
This article examines the corporate responsibilities of Indonesian state-owned enterprises (BUMN) concerning employee status following a spin-off, specifically the transformation of PT Perkebunan Nusantara III (Persero) Operational Medan into PT Perkebunan Nusantara IV Regional I. Spin-offs often involve organizational restructuring, which may impact employees’ employment status, contracts, and entitlements. Current Indonesian labor regulations, including the Labor Law and the Omnibus Law, do not provide explicit legal certainty for employees in spin-off scenarios, while the Limited Liability Company Law primarily governs asset and liability allocation rather than employee rights. This study analyzes the legal framework, company practices, and challenges in safeguarding employees’ rights during the spin-off process. The findings indicate that employees face uncertainty regarding job security, benefits, and contractual terms due to ambiguous clauses in existing agreements and insufficient regulatory guidance. To address these issues, the study recommends establishing specific regulations for spin-offs, ensuring continuity of employment contracts, strengthening labor supervision, involving trade unions in decision-making, and providing training programs to enhance employee resilience. Government involvement is also critical to monitor compliance and mediate potential disputes. In conclusion, creating clear legal frameworks and corporate policies for spin-offs is essential to guarantee employees’ legal certainty, uphold industrial harmony, and fulfill BUMN’s social responsibilities. Proper implementation ensures that operational efficiency is balanced with the protection of employee rights, promoting sustainable business practices in state-owned enterprises.